2020
DOI: 10.5195/ijt.2020.6321
|View full text |Cite
|
Sign up to set email alerts
|

Development and Feasibility Testing of Video Home Based Telerehabilitation for Stroke Survivors in Resource Limited Settings

Abstract: Tele-physiotherapy has been shown to be valuable to improve clinical outcomes after stroke. Yet, home-based interventions for stroke survivors (SSVs) who speak indigenous African languages are sparse. This study developed a video-based home exercise programme (VHEP) for SSV speakers of Yoruba.  A qualitative descriptive pilot study was conducted in two phases: development and feasibility testing. VHEP development followed the American Stroke Association’s recommendations to include demonstrations of task-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Only the levels of education showed significant increase with identification of stroke risk factors and warning signs, between the primary and the tertiary levels of education 2 nd week post-intervention. These findings are consistent with previous studies on stroke education of Denny et al, 30 and Maisarah et al, 36 . Earlier studies, have reported increase in stroke knowledge across education levels, with the largest effect on those with at least college education.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Only the levels of education showed significant increase with identification of stroke risk factors and warning signs, between the primary and the tertiary levels of education 2 nd week post-intervention. These findings are consistent with previous studies on stroke education of Denny et al, 30 and Maisarah et al, 36 . Earlier studies, have reported increase in stroke knowledge across education levels, with the largest effect on those with at least college education.…”
Section: Discussionsupporting
confidence: 94%
“…The choice of mobile phones as an easy means of information delivery is supported by similar reports of no difficulty with operating the exercise package on the mobile device or at home. 32, 35 The educational tool in this study was of 14-minute duration, in contrast to a stroke literacy video of 5-minute duration by Denny et al, 9 and a 30-minute video home-based exercise for SSVs by Odetunde et al, 36 The varied duration was to address the study objectives and accommodate the contents of each of the videos. This study revealed that the AVmHealth stroke education was associated with improved stroke literacy at the 2 nd and 4 th week post intervention, consistent with previous studies on stroke education.…”
Section: Discussionmentioning
confidence: 99%
“…This review identified 16 studies that investigated the feasibility of TR programs for neurological conditions, 16 19 , 21 , 23 25 , 28 , 31 medical conditions, 20 , 22 , 27 , 30 neuromusculoskeletal disorders, 29 as well as older people. 26 Fourteen (14) out of 16 studies 16 20 , 22 , 23 , 25 31 were conducted in HICs and only 2 studies 21 , 24 in LMICs.…”
Section: Resultsmentioning
confidence: 99%
“…This review identified 16 studies that investigated the feasibility of TR programs for neurological conditions, 16 19 , 21 , 23 25 , 28 , 31 medical conditions, 20 , 22 , 27 , 30 neuromusculoskeletal disorders, 29 as well as older people. 26 Fourteen (14) out of 16 studies 16 20 , 22 , 23 , 25 31 were conducted in HICs and only 2 studies 21 , 24 in LMICs. Feasibility was determined by recruitment rate, retention rate, attendance/adherence to the program, completion rate, satisfaction, adverse events and technical faults during the implementation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation